Sociodemographic and clinical predictors of HIV-AIDS among clients in the HKBP AIDS Ministry - FBA Ummiyah; Lubis, Rahayu (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to determine the factors related to the incidence of HIV and AIDS among people living with HIV/AIDS (PLWHA) at the HKBP (Huria Kristen Batak Protestan) AIDS Ministry in 2019–2021, as the only institution established to provide assistance and empowerment to PLWHA in the Toba Regency. Methods: This research employs an analytical, quantitative approach with a cross-sectional design. The sample consisted of 172 respondents aged 15 to 64 years who were selected as participants. The study's results were derived from data collected through interviews that utilized questionnaires, which were then analyzed using both univariate and bivariate analysis, including a chi-square statistical test. Results: The results showed that the proportion of HIV incidence was 79.7% and AIDS incidence was 20.3%. The results of bivariate analysis showed that there was a significant relationship between the variable history of infectious diseases (p < 0.001) and the incidence of HIV and AIDS. There was no significant relationship between the variables gender (p = 0.462), education level (p = 0.859), occupation (p = 0.462), mode of transmission (p=0.254), and knowledge (p = 0.225) with the incidence of HIV and AIDS in the HKBP AIDS Ministry in 2019-2021. Conclusion: People who have a history of infectious diseases are at the highest risk of contracting HIV in the AIDS Ministry. Patients are expected to consume antiretroviral therapy routinely and pay more attention to handling and management of infectious diseases when having sexual intercourse.